1998
DOI: 10.1016/s0960-9822(07)00491-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour in Drosophila is irreversibly programmed during a critical period

Abstract: Sexual differentiation in Drosophila is controlled by a short cascade of regulatory genes, the expression pattern of which determines all aspects of maleness and femaleness, including complex behaviours displayed by males and females [1-3]. One sex-determining gene is transformer (tra), the activity of which is needed for female development. Flies with a female karyotype (XX) but which are mutant for tra develop and behave as males. In such flies, a female phenotype can be restored by a transgene that carries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 21 publications
(31 reference statements)
6
39
1
4
Order By: Relevance
“…The function of P1 promoter is restricted to ~2% of neurons in the CNS, in various regions of the brain and ventral ganglia, from late third instar larva onward (reviewed in Billeter et al, 2002;. To this respect, it is worth mentioning that sexual behaviour of the Drosophila male is irreversibly programmed during a critical period extending from shortly before puparium formation into early metamorphosis (Arthur et al, 1998). Sexual behaviour, however, is not reviewed here.…”
Section: The Sex-determining Genetic Cascade Of Drosophila Melanogastermentioning
confidence: 99%
“…The function of P1 promoter is restricted to ~2% of neurons in the CNS, in various regions of the brain and ventral ganglia, from late third instar larva onward (reviewed in Billeter et al, 2002;. To this respect, it is worth mentioning that sexual behaviour of the Drosophila male is irreversibly programmed during a critical period extending from shortly before puparium formation into early metamorphosis (Arthur et al, 1998). Sexual behaviour, however, is not reviewed here.…”
Section: The Sex-determining Genetic Cascade Of Drosophila Melanogastermentioning
confidence: 99%
“…These include mutations in genes required for normal morphology [white (13,14), yellow (14), and curved (15)], as well as genes involved in learning and memory [Calcium calmodulin kinase II (16), dunce (17,18), rutabaga (19,20), turnip (19,21), and amnesiac (20,22,23)], circadian rhythm [period (18,(24)(25)(26)] and dopamine and serotonin synthesis [Dopa decarboxylase (27), pale (28,29), tan (30,31), and ebony (32)(33)(34)], sex determination [doublesex (35)(36)(37), transformer (38)(39)(40)(41)(42)(43), fruitless (44)(45)(46)(47), and sex lethal (48)], pheromone production [desaturase 2 (49)], and accessory gland-specific peptides (6-8, 50-52). a subset of loci identified by mutational analysis, or will the analysis of natural variants reveal novel loci?…”
Section: Drosophila Mating Behaviormentioning
confidence: 99%
“…The fru gene encodes a predicted BTB/POZ family zinc-finger transcription factor, which has been shown to be a member of the D. melanogaster somatic sex determination hierarchy (Ito et al 1996;Ryner et al 1996;Heinrichs et al 1998). The use of an antibody specific to male-limited FRU proteins (FRU M ) (Lee et al 2000;Lee and Hall 2001) has demonstrated that the spatial and temporal distribution of FRU M proteins in the CNS is consistent with the timing of the critical period for programming a male fate (Belote and Baker 1987;Arthur et al 1998) and the regions of the CNS whose maleness is necessary for normal development of male courtship behaviors (Hall 1979;von Schlicher and Hall 1979). Most recently, it has been shown that sex-specific splicing of fru specifies the male courtship behavior fate (Demir and Dickson 2005;Manoli et al 2005;Stockinger et al 2005).…”
Section: R Eproduction Usually Involves Heterosexual Court-mentioning
confidence: 99%